Strategi Pengembangan DTW Pantai Diamond di Dusun Pelilit, Desa Pejukutan, Nusa Penida, Klungkung, Bali - Listiowati, Agnela Saneta; Wiranatha, Agung Suryawan; Suryawardani, I Gusti Ayu Oka (JURNAL MASTER PARIWISATA; Volume 06, Nomor 02, Januari 2020, 2020)
Diamond Beach is located at Pelilit Village, Pejukutan Village, Nusa Penida District. This tourist attraction was developed since 2014. Even though it have been developed since five years ago, there is still bad perception from local community about the components at Diamond Beach, in specific about amenity, accessibility, and human resource. Those local community perception contrasts with the perception of tourists that visited Diamond Beach, which they have good perception of all destination components in Diamond Beach. This research used qualitative descriptive approach that concerned about the perception of tourist and local community towards destination component at Diamond Beach. All perceptions and collected data using triangulation were used to identify internal and external environment condition at Diamond Beach. Result of internal and external factor analysis at Diamond Beach were both in medium condition. Then, the proper grand strategy to be applied in next level is keeping up and maintaining without changing the strategy that has been used before. This grand strategy is stressing more about product and service development, also market penetration. Keywords: perception, development strategy, tourist attraction